Avaliação da Eficácia da Cissus verticillata (L.), em Portadores de Diabetes Melito tipo 2, através da concentração de glicose na saliva e no sangue - Rosendo, Rosana Araújo (2009)
The study objectived administer the infuso sheets Cissus verticillata (L.) in patients with diabetes type 2 melito, to investigate the therapeutic efficacy of this plant in these patients, by testing glucose concentration in the blood and saliva. It is a clinical experimental study, comparison and longitudinal type descriptive, developed in the municipal district of Patos-PB. Patients were included in the search for both sexes, included aged between 30 and 80 years old, divided into two groups, with a control group mid-cap glibenclamida and an experimental group used the infuso of Cissus verticillata (L.) in fasting, for a period of eight weeks. Clinical patient assessment, both groups, was formed from the analysis of the levels of glucose in the blood and saliva. The results showed that the infuso of Cissus verticillata (L.) was able to produce an effect hypoglycaem ic in experimental group. Salivary levels, when collected at rest, higher averages in basal assessments control group, 15 days and 60 days and, when collected under stimulus masticatory made correspondingly higher average in the experimental group, with the exception of basal, no assessment demonstrating significant difference between the groups to none of the trials (p > 0,05). The correlation between the rate of blood capillary blood glucose concentration and salivary was not observed in this study.